13.4 % Efficiency from All‐Small‐Molecule Organic Solar Cells Based on a Crystalline Donor with Chlorine and Trialkylsilyl Substitutions. Issue 17 (19th June 2021) - Su, Wenyan; Wang, Yang; Yin, Zhihong; Fan, Qunping; Guo, Xia; Yu, Liyang; Li, Yuxiang; Hou, Lintao; Zhang, Maojie; Peng, Qiang; Li, Yongfang; Wang, Ergang
Abstract: How to simultaneously achieve both high open‐circuit voltage ( V oc ) and high short‐circuit current density ( J sc ) is a big challenge for realising high power conversion efficiency (PCE) in all‐small‐molecule organic solar cells (all‐SM OSCs). Herein, a novel small molecule (SM)‐donor, namely FYSM−SiCl, with trialkylsilyl and chlorine substitutions was designed and synthesized. Compared to the original SM‐donor FYSM−H, FYSM−Si with trialkylsilyl substitution showed a decreased crystallinity and lower highest occupied molecular orbital (HOMO) level, while FYSM−SiCl had an improved crystallinity, more ordered packing arrangement, significantly lower HOMO level, and predominant "face‐on" orientation. Matched with a SM‐acceptor Y6, the FYSM−SiCl‐based all‐SM OSCs exhibited both high V oc of 0.85 V and high J sc of 23.7 mA cm −2, which is rare for all‐SM OSCs and could be attributed to the low HOMO level of FYSM−SiCl donor and the delicate balance between high crystallinity and suitable blend morphology. As a result, FYSM−SiCl achieved a high PCE of 13.4 % in all‐SM OSCs, which was much higher than those of the FYSM−H‐ (10.9 %) and FYSM−Si‐based devices (12.2 %). This work demonstrated a promising method for the design of efficient SM‐donors by a side‐chain engineering strategy via the introduction of trialkylsilyl and chlorine substitutions. Abstract : Superb substitution : A small molecule donor FYSM−SiCl with trialkylsilyl and chlorine substitutions is developed. Compared to its unsubstituted analogue FYSM−H, FYSM−SiCl has a deep‐shifted highest occupied molecular orbital level, improved crystallinity and hole‐mobility, and a predominantly "face‐on" orientation. FYSM−SiCl‐based all‐small‐molecule solar cells achieve a much higher power conversion efficiency of 13.4 % compared to the FYSM−H‐based ones (10.9 %).